An innovative process for dispersion of graphene nanoparticles and nickel spheres in A356 alloy using pressure infiltration technique. Issue 1 (17th January 2020) - Das, Sourav; Kordijazi, Amir; Akbarzadeh, Omid; Rohatgi, Pradeep K.
Abstract: In this paper, a unique, innovative liquid metal infiltration process for the dispersion of graphene in the aluminum (Al) matrix in the presence of nickel spheres is introduced. The nickel spheres impart a reaction that induces wettability with molten Al, hence facilitating the infiltration of Al encapsulating graphene. Raman spectroscopy shows the two‐dimensional bands, thereby confirming the presence of graphene in the infiltrated composite. The microstructure of the infiltrated composite shows the dispersion of graphene, Al‐silicon eutectic, and a reaction product between nickel and Al around nickel spheres. The sample of composite tested in this study exhibits a high contact angle and hydrophobicity, possibly due to the dispersion of graphene particles on the surface of the samples. This presence of graphene on the surface causes a reduction of wetting by water and a decrease in corrosion rate which is demonstrated by polarization testing results. Abstract : A pressure infiltration technique was used to manufacture a composite material. A distribution of graphene and nickle spheres were achieved throughout the A356 alloy surface. The process leads to a hydrophobic surface.